Biomedical equipment for the control of nutrition and for the physical exercise of people with diabetes - Mantilla Guerra, Aníbal Rubén (Enfoque UTE, 2017)
In order to contribute to the treatment of diabetes, which is one of the main causes of death in Ecuador and in the world, a research project is being developed to create equipment that allows the effective control and treatment of this disease. The electronic equipment created for nutrition control, allows the diabetic patient to have information about the amount of calories they should ingest in consideration of their activities and their medical treatment. The mechatronic equipment for the physical exercise of people with diabetic foot, allows the application of therapies according to the severity of the affection. Considering that this is a delicate and complex treatment, the equipment helps the patients to alleviate its discomfort, to decrease the time of recovery and in some cases even to avoid amputation. The construction of the biomedical equipment for the control of nutrition is completed. While the equipment for the treatment of diabetic foot is in a stage of development of prototypes and tests. Both equipment has been conceived and developed with rigorous engineering methods and under quality standards, making an important contribution to research, development of science, technology, and innovation.